Barium carbonate and supplementary cementitious materials to counteract thaumasite sulfate attack in mortars: Effect of aggregate composition. (3rd May 2021) - Carmona-Quiroga, P.M.; Blanco-Varela, M.T.
Highlights: The potential of BaCO3 aggregate to counteract sulfate attack was explored. BaCO3 sand enhanced the sulfate -resistance of commercial SR cement. At 8 °C, soluble barium failed to neutralise a highly concentrated sulfate attack. Abstract: Supplementary cementitious materials (SCMs) have been shown to have a beneficial impact on carbonate-bearing mortar and concrete resistance to sulfates in general and thaumasite sulfate attack (TSA) in particular, although the effect is limited in some cases. In pursuit of improved sulfate-resistance formulations that inhibit thaumasite formation, this study added barium carbonate, both as mineral addition and as aggregate, to cements blended with SCMs. The aim was to immobilise sulfates via conversion to barite, a practically insoluble form of barium sulfate. The study was conducted on standardised mortars prepared with CEM I 52.5 N-SR 5 (reference, Ref) cement, laboratory-blended CEM III/C-SR (with slag) or CEM IV/B-SR (fly ash-bearing) cements. Mixes were also prepared with the latter two cements in which the slag or fly ash filler was partially replaced with barium carbonate. Barium or calcium carbonate sands were used as aggregate in the respective mortars, all of which were soaked in a Na2 SO4 solution at 8 °C for 6 months and monitored for variations in mass, compressive strength, ultrasonic velocity, soundness (expansion) and mineralogy. The findings showed that at such low temperatures the amount of Ba 2+ solubilised did not suffice to effectively immobilise the external sulfates in the blends containing SCMs. The fly ash-bearing samples, particularly where the addition was partially replaced with barium carbonate, deteriorated severely or very severely (substantial expansion and mass loss) because thaumasite precipitated even in the presence of the barite formed. The low cement content, slag-bearing blends exhibited greatest sulfate resistance, irrespective of the presence of barium carbonate as addition or aggregate. In mortars made with commercial, low C3 A content (Ref.) sulfate-resistant cement, barium carbonate sand inhibited gypsum and ettringite formation, whereas both products precipitated in analogous and less porous mixes bearing limestone aggregate.